Method for preparing solid electrolyte by utilizing sludge of gravel processing system
Solid electrolytes are prepared by calcining the sludge of the sand and gravel processing system with silicate cement and conductive materials at high temperature, and the problems of sludge treatment and electrical energy storage are solved, and the efficiency of sludge resource utilization and electrical energy storage is achieved.
Patent Information
- Application Number
- CN202411238713.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-05
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-05
AI Technical Summary
The sludge produced by the sand and gravel processing system has ecological hazards, pollution problems and is difficult to use in resource utilization. Pumped energy storage technology wastes hydraulic resources and fails to effectively solve the storage problems of electricity and renewable energy.
The sludge of the sand and gravel processing system is dried and crushed and pretreated, silicate cement and conductive materials are added, and solid electrolyte materials are prepared by high-temperature calcination, which is used to prepare solid supercapacitors or batteries, and is combined with wireless charging technology.
The harmless treatment and resource utilization of sludge have been achieved, and solid electrolyte materials can be developed that can be used to store electricity and renewable energy, which improves the efficiency of electricity storage and the utilization of renewable energy, and avoids waste of water resources.
Smart Images

Figure CN119230304A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sludge resource utilization, in particular to a method for preparing solid electrolytes by utilizing sludge from a sandstone processing system. Background Art
[0002] Large hydropower stations or construction sites use biotite quartz schist excavated from engineering projects as the source of materials for the production of sand and gravel aggregates. The wastewater generated by the sand and gravel system is mainly the wastewater generated by the washing of crushed stones in the crushing workshop, the washing of coarse aggregates in the screening workshop, the washing of finished sand, and the water used for dust reduction and cleaning in each workshop. The sludge generated by the treated wastewater of the sand and gravel processing system is pressed into the box frame filter press by a slurry pump. The sludge is dried and transported to the waste dump, which not only poses ecological hazards but also easily causes secondary pollution. It will cause certain pollution to the air, soil and groundwater, and will occupy a large area of land. The pH of the sludge exceeds the standard, the organic matter content is very low, the effective nitrogen, phosphorus and potassium do not meet the requirements of plant growth, and lack the nutrient components necessary for plant growth. The soil has low porosity, poor agglomeration, poor water retention and poor air permeability. Some heavy metals exceed the standard and have strong biological toxicity. The disposal of sludge from wastewater treatment in the sand and gravel processing system has always been a problem that has plagued the production of artificial sand and gravel processing systems.
[0003] Pumped storage is the mainstream technology for large-scale energy storage in hydropower stations. It has the advantages of large energy storage capacity, high system efficiency, long operating life, and mature technology. However, pumped storage is only for the storage of electricity in different periods, and it wastes a lot of water resources, and does not fundamentally solve the storage problem of electricity and renewable energy. If solid electrolytes or cement-based solid electrolytes can be developed, and the sludge and cement produced in the sand and gravel processing system during the construction of hydropower stations can be converted into solid electrolyte materials for supercapacitors or batteries, it will be of epoch-making significance for the storage of hydropower and renewable energy. Combined with wireless charging technology, roads and buildings can be transformed into charging and discharging energy storage systems. Summary of the invention
[0004] In order to achieve harmless treatment and resource utilization of sludge in a sand and gravel processing system, the present invention provides a method for preparing a solid electrolyte by utilizing the sludge in a sand and gravel processing system.
[0005] The method for preparing solid electrolyte using sludge from a sand and gravel processing system provided by the present invention mainly comprises the following steps: drying and crushing the sludge from the sand and gravel processing system for pretreatment, adding silicate cement and a conductive material to the pretreated sludge, mixing them evenly, and then calcining the mixture at 750-850° C. for 1-2 hours under a nitrogen protection environment to obtain an electrolyte material. The conductive material is preferably conductive charcoal powder or kitchen waste compost carbonized powder.
[0006] The electrolyte material can be further used to prepare a solid-state supercapacitor or solid-state battery. The electrolyte material, positive electrode and negative electrode are assembled to form a solid-state battery or capacitor. This capacitor can be used as wall tiles, floor tiles, and pavement tiles, and can be combined with renewable energy to form energy storage capacitors and wireless charging devices.
[0007] The electrolyte preparation method can be specifically carried out according to the following two methods.
[0008] Method 1, the steps are as follows:
[0009] S1. Pretreatment of sludge from sand and gravel processing system: The sludge produced after wastewater treatment in a sand and gravel processing system of a hydropower station is naturally dried until the sample reaches a constant weight (the mass change of the sludge does not exceed 1%), and then crushed.
[0010] S2. Add acid to the sludge in the sand and gravel processing system, stir for 10-30 minutes, filter out insoluble matter, and obtain a solution.
[0011] The acid solution is selected from any one of hydrochloric acid, nitric acid and sulfuric acid or a mixture of two thereof.
[0012] The sludge from the sand and gravel processing system is dissolved by hydrochloric acid, mainly to remove some components that are not suitable for solid electrolytes, and retain the active elements required for solid electrolysis, such as lithium, yttrium, iron and other active components of electrolytes. When hydrochloric acid is used for dissolution, chloride ions can also be added to partially form halide electrolyte materials.
[0013] S3. Add thiosulfate to the solution obtained in step S2, and then add urea or potassium hydroxide to make the solution alkaline to precipitate a precipitate, filter, and dry the precipitate.
[0014] Thiosulfate is added in this step to form a partial sulfide metal salt electrolyte material, which becomes a sulfide electrolyte with high conductivity. Urea is added to form a precipitate to further form various active metal elements bridged and coordinated by nitrogen atoms, thereby improving electrical conductivity and energy storage efficiency.
[0015] S4. Add silicate cement, potassium hydroxide and conductive material to the dried precipitate, mix well, and calcine the mixture at 750-850° C. for 1-2 hours in a nitrogen protection environment to obtain an electrolyte material.
[0016] In this step, cement and sand processing system sludge are added to prepare cement-based solid electrolytes to improve the conductivity of solid electrolytes. The high-temperature calcination process can remove moisture and polymerize different electrolyte materials, increase specific surface area and porosity, and increase conductive energy storage.
[0017] Preferably, in step S2, the volume ratio of the sludge in the sand and gravel processing system to the acid solution is 1:(3-5).
[0018] It is further preferred that the acid solution is concentrated hydrochloric acid with a mass fraction of hydrogen chloride of 36% to 38%.
[0019] Preferably, in step S4, the amount of silicate cement added is 5-35% of the mass of the precipitate, and the amount of potassium hydroxide added is 1-3% of the mass of the precipitate.
[0020] The conductive material is conductive charcoal powder (carbon black) or kitchen waste compost carbonized powder, and the amount of conductive material added is 1.5-5% of the mass of the precipitate. Humic acid and carbon black in kitchen waste compost can increase the energy storage and gap of electrolytes, and increase ion migration, conversion and aggregation.
[0021] Method 2, the steps are as follows:
[0022] S1. Dry and crush the sludge from the sand and gravel processing system for pre-treatment.
[0023] S2. Add lithium salt, water, silicate cement and conductive material to the pretreated sludge from the sand and gravel processing system, mix and stir for 10-30 minutes, and calcine the mixture at 750-850° C. for 1-2 hours under a nitrogen protection environment to obtain an electrolyte material.
[0024] Compared with the prior art, the present invention is beneficial in that:
[0025] The present invention prepares solid electrolyte materials by using useful components in the sludge of the sand and gravel processing system, thereby not only realizing the resource utilization of the solid waste of the sludge of the sand and gravel processing system, but also realizing the multifunctional application of cement-based composite materials.
[0026] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a scanning electron microscope image of the electrolyte material powder prepared in Example 1.
[0028] Figure 2 This is a transmission electron microscope image of the electrolyte material powder prepared in Example 1. DETAILED DESCRIPTION
[0029] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0030] Example 1
[0031] A method for preparing solid electrolyte using sludge from a sand and gravel processing system, comprising the following steps:
[0032] (1) Pretreatment of sludge from sand and gravel processing system: The sludge produced after wastewater treatment in the sand and gravel processing system of a hydropower station was naturally dried until the sample reached a constant weight (the mass change of the sludge did not exceed 1%), and then crushed.
[0033] (2) Add concentrated hydrochloric acid with a concentration of 36% to 38% to the pretreated sludge from the sand and gravel processing system, with the volume ratio of sludge to concentrated hydrochloric acid being 1:4, and stir for 30 minutes. Filter and remove insoluble matter to obtain solution A. Take 1 L of solution A, add 1.5 mol of sodium thiosulfate, and add urea to adjust the pH of the solution to greater than 9. A large amount of precipitate precipitates in the solution. Filter, collect and dry the precipitate.
[0034] (3) Add silicate cement and a small amount of potassium hydroxide to the dried precipitate, wherein the amount of silicate cement accounts for 25wt% of the mass of the precipitate and the amount of potassium hydroxide accounts for 1wt% of the mass of the precipitate. After mixing evenly, add conductive charcoal powder (carbon black), wherein the amount of conductive charcoal powder (carbon black) accounts for 4wt% of the mass of the precipitate. After mixing evenly, place in a high-temperature furnace and calcine at 800°C for 1h under nitrogen protection to prepare an electrolyte material.
[0035] (4) The electrolyte material is taken out from the high-temperature furnace while it is still hot and quickly poured into a brick-making mold. When it has not yet completely hardened and has good fluidity, two electrodes (stainless steel sheets or other electrodes) are placed on both sides of the electrolyte. After the slurry hardens, an integrated supercapacitor is formed.
[0036] The scanning electron microscope and transmission electron microscope images of the electrolyte material powder prepared in Example 1 are as follows: Figure 1 and 2 shown.
[0037] In order to analyze the surface morphology of the solid electrolyte powder and determine the structure of the prepared product, the electrolyte powder treated at 800°C with good effect (electrolyte powder prepared in Example 1) was selected for scanning electron microscope test to observe its surface morphology and structure. Figure 1 (a) shows the particle agglomerates of different sizes, which can be observed by magnifying them 4,000 times. Figure 1 (b) In the area shown in the picture, a graphene-like layered structure can be clearly observed, generating the expected layered structure. Further magnification of 20,000 times yields Figure 1 (c) and Figure 1 (d) From the structural cross-section in the figure, it can be found that the structure has an obvious layered structure, and tiny powder particles are attached to its surface. Combined with the XRD spectrum analysis results, it can be considered that the solid electrolyte was successfully prepared.
[0038] Figure 2The darker colored area has good conductivity, while the lighter colored area has poor conductivity. From the XRD spectrum, we can see that the part with good conductivity is mainly composed of NASCION-type stoichiometric ratio. Figure 2 As shown in (a), crystal agglomeration occurs in some areas, and the surrounding areas are accompanied by pore structures generated by sintering. Although the existence of pore structures may help reduce the impact of volume changes, according to Figure 2 As shown in (b) and (c), the sintered pore area seems to be more prone to agglomeration, which obviously has an adverse effect on the conductivity of the electrolyte; further zooming in, such as Figure 2 The solid electrolyte particles shown in (d) have a thin carbon coating layer. Combined with the SEM image results, the overall results indicate that the solid electrolyte structure was successfully synthesized.
[0039] The electrochemical performance of the supercapacitor was tested using an electrochemical workstation (Shanghai Chenhua 660e). The ionic conductivity of the solid electrolyte prepared by the above method was 192.3-564.7 mS·cm -1 . When a constant changing voltage is applied, the current corresponding to the supercapacitor can basically reach a constant value instantly. When the voltage is reversed, the current instantly returns to the corresponding negative constant value. Cement-based supercapacitors can output current sustainably and stably, with a charge and discharge time of 31-58s, good capacitive behavior, a specific capacitance of 85F / g-115F / g, an internal resistance of 26.6Ω-39.8Ω, an interface resistance of 6.7Ω-30.5Ω, and low resistance to ion diffusion and migration in the electrolyte in the low-frequency region.
[0040] The voltage of the capacitor is 0.8-1.1U(V), the current can reach 5.3-7.8mA, and the specific capacity reaches 131-210mAh / g. When the current density is 0.5A·g -1 When the structure supercapacitor has 95.6F·g -1 The high specific capacitance, after 2000 cycles of constant current charge and discharge, the capacitance retention rate reached 76.2% and the coulomb efficiency was 87.1%, showing a good cycle life.
[0041] Example 2
[0042] A method for preparing solid electrolyte using sludge from a sand and gravel processing system, comprising the following steps:
[0043] (1) Pretreatment of sludge from sand and gravel processing system: The sludge produced after wastewater treatment in the sand and gravel processing system of a hydropower station was naturally dried until the sample reached a constant weight (the mass change of the sludge did not exceed 1%), and then crushed.
[0044] (2) Add lithium chloride, water, silicate cement and conductive charcoal powder (carbon black) to the pretreated sludge and stir for 30 minutes to mix evenly; the amount of lithium chloride added accounts for 5wt% of the sludge weight, the amount of water added accounts for 10wt% of the sludge weight, the amount of silicate cement added accounts for 15wt% of the sludge weight, and the amount of conductive charcoal powder added accounts for 1.0wt% of the sludge weight; place the mixture in a high-temperature furnace and calcine it at 750°C for 2h under nitrogen protection to prepare an electrolyte material.
[0045] (3) The electrolyte material is taken out from the high-temperature furnace while it is still hot and quickly poured into a brick-making mold. When it has not yet completely hardened and has good fluidity, two electrodes (stainless steel sheets or other electrodes) are placed on both sides of the electrolyte. After the slurry hardens, an integrated supercapacitor is formed.
[0046] The electrochemical performance of the supercapacitor was tested using an electrochemical workstation (Shanghai Chenhua 660e), and the ionic conductivity of the solid electrolyte was 91.7-298.6 mS·cm -1 The obtained supercapacitor has a specific capacitance of 598-782F / V, an electrolyte resistance of 19.1Ω-31.7Ω, and a charge transfer resistance of 11.6Ω-51.2Ω. After 2000 cycles of constant current charge and discharge, the capacitance retention rate reached 86.1-95.3%, and the coulomb efficiency was 81.6-91.2%, showing a good cycle life.
[0047] Durability testing, water resistance testing, and drying shrinkage testing have demonstrated good adaptability and the ability to adapt to changing requirements in high-cold areas and high and low temperatures.
[0048] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing solid electrolyte using sludge from a sand and gravel processing system, characterized in that: The sludge from the sand and gravel processing system is dried and crushed for pretreatment, silicate cement and conductive material are added to the pretreated sludge, and after uniform mixing, the mixture is calcined at 750-850° C. for 1-2 hours in a nitrogen protection environment to obtain an electrolyte material; the conductive material is conductive charcoal powder or kitchen waste compost carbonized powder.
2. The method for preparing solid electrolyte using sludge from a sand and gravel processing system according to claim 1, characterized in that: The following steps are involved: S1. Drying and crushing the sludge from the sand and gravel processing system for pre-treatment; S2. Add acid to the pretreated sludge from the sand and gravel processing system, stir for 10-30 minutes, filter to remove insoluble matter, and obtain a solution; S3, adding thiosulfate to the solution obtained in step S2, and then adding urea or potassium hydroxide to make the solution alkaline to precipitate a precipitate, filtering, and drying the precipitate; S4. Add silicate cement, potassium hydroxide and conductive material to the dried precipitate, mix well, and calcine the mixture at 750-850° C. for 1-2 hours in a nitrogen protection environment to obtain an electrolyte material.
3. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 2, characterized in that: In step S1, the acid solution is selected from any one of hydrochloric acid, nitric acid, and sulfuric acid, or a mixture of two of them.
4. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 3, characterized in that: The volume ratio of sludge to acid in the sand and gravel processing system is 1:(3-5).
5. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 2, characterized in that: In step S3, the amount of silicate cement added is 5-35% of the mass of the precipitate.
6. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 2, characterized in that: In step S3, the amount of potassium hydroxide added is 1-3% of the mass of the precipitate.
7. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 2, characterized in that: The amount of the conductive material added is 1.5-5% of the amount of the precipitate.
8. The method for preparing solid electrolyte using sludge from a sand and gravel processing system as claimed in claim 1, characterized in that: The following steps are involved: S1. Drying and crushing the sludge from the sand and gravel processing system for pre-treatment; S2. Add lithium salt, water, silicate cement and conductive material to the pretreated sludge from the sand and gravel processing system, mix and stir for 10-30 minutes, and calcine the mixture at 750-850° C. for 1-2 hours under a nitrogen protection environment to obtain an electrolyte material.
9. The method for preparing solid electrolyte using sludge from a sand and gravel processing system according to claim 1, characterized in that: The prepared electrolyte material, positive electrode and negative electrode are assembled into a solid-state battery or capacitor.
Citation Information
Patent Citations
Polyacrylamide / magnesium phosphate cement composite solid electrolyte, preparation method thereof and structural supercapacitor
CN115424872A
Structural supercapacitor based on redox cement-based solid electrolyte and preparation method thereof
CN116313554A
Solid electrolyte material and preparation method and application thereof
CN117174995A
